Post-operative Recovery of Morbidly Obese Patients under General Anaesthesia Using Desflurane versus Sevoflurane (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Laparoscopic sleeve gastrectomy (LSG) is commonly performed under general anaesthesia. LSG operation has become one of the most effective treatments of morbidly obese patients. There are several modalities of inducing and maintenance of general anaesthesia (GA).Objectives: To compare the post-operativerecovery of morbidly obese patient using desflurane versus sevoflurane with remifentanyl infusion as maintenance of anaesthesia.Materials and Methods: This prospective randomized singlecentre analytic study was carried out in Jaber Al Ahmed Armed Forces Hospital, Kuwait from July 2015 to July 2017. Total 60 morbidly obese patients(BMI>40kg/m2) undergoing LSG under GA were randomly selected into two equal groups(Group-A and Group-B).Group-A received desflurane, Group-B received sevoflurane and both groups receivedremifentanyl infusion as maintenance of GA. To maintain hemodynamic stability and bispectral index score in the range of 40-60, using volatile anaesthetic either desflurane 2-6% or sevoflurane 1-2% with airand oxygen 50: 50 during maintenance. Early recovery criteria were response to painful stimuli,obeying verbal command, spontaneous eye-opening, extubation time, handgrip, and orientation assessed by answering name and location. Intermediate recovery was assessed by modified Aldrete’sscore at PACU.Results: No significant differences in perioperative heart rate, systolic blood pressure, and diastolic blood pressurewas found between two groups. Group-A patients had significantly faster eye-opening (9.7±4.3 vs 18.5±6.6),voluntary head rising on command (3.46±2.1 vs 7.38±4.52) shorter extubation time(12.2±8.1 vs 24.2±12), and orientation in time(16.2±8.2 vs 31.2±12.9)as compared to Group-B.Conclusion: Volatile anaestheticdesflurane provided better post-operative recovery than sevoflurane in morbidly obese patients undergoing LSG with GA.Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 116-119